2017
DOI: 10.1039/c7rp00062f
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of case-based instruction on electrochemistry at the 11th grade level

Abstract: This study aims to compare the effectiveness of case-based instruction over traditional instruction in improving 11th grade students' understanding of electrochemistry concepts, attitudes toward chemistry, chemistry self-efficacy beliefs, and motivation to learn chemistry. In total, 113 students (47 males and 66 females) from three high schools participated in this study. Two of the classes from each school were randomly assigned to be either the experimental or control group. The experimental group was instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 102 publications
3
30
0
Order By: Relevance
“…(S17) While majority of students expressed positive views about the CBL method like teachers' leadership, self-learning, mutual information sharing and having no difficulty in application due to the intriguing and successful case study; only four students expressed negative views and they believed that the method would be time-consuming due to new concepts and difficulty of solving incoherent parts. In his study; Tarkın (2014) concluded that majority of students expressed positive opinions about the CBL method as they had no difficulty, whereas some of them expressed negative opinions as they had difficulties in group work, interpretation of case studies and question-answer sections. In general, majority of students expressed positive views as they could cooperate in group work, exchange information, communicate, find a solution by creating a discussion environment in a short time and have fun.…”
Section: Results Concerning Cbl Method Group Work and The Applicatiomentioning
confidence: 99%
“…(S17) While majority of students expressed positive views about the CBL method like teachers' leadership, self-learning, mutual information sharing and having no difficulty in application due to the intriguing and successful case study; only four students expressed negative views and they believed that the method would be time-consuming due to new concepts and difficulty of solving incoherent parts. In his study; Tarkın (2014) concluded that majority of students expressed positive opinions about the CBL method as they had no difficulty, whereas some of them expressed negative opinions as they had difficulties in group work, interpretation of case studies and question-answer sections. In general, majority of students expressed positive views as they could cooperate in group work, exchange information, communicate, find a solution by creating a discussion environment in a short time and have fun.…”
Section: Results Concerning Cbl Method Group Work and The Applicatiomentioning
confidence: 99%
“…Regarding procedural difficulties, the most documented one was related to associating the redox concepts with the observed phenomena. Tarkin and Uzuntiryaki-Kondakci (2017) reported that students had difficulty applying their theoretical knowledge about oxidationreduction concepts when interpreting daily life events. Cole et al (2019), Haigh et al (2012), Kelly et al (2017) and Testa et al (2018) identified that students were not able to correctly correlate the color change with the oxidation / reduction of the substance.…”
Section: Limitations Of Teaching and Learning Redox Reactionsmentioning
confidence: 99%
“…Cole et al (2019);Haigh et al (2012);Kelly et al (2017);Koenig et al (2019);Llanos et al (2019);Lee (2007);Niaz and Chacón (2003);Tarkin and Uzuntiryaki-Kondakci (2017); Testa et al(2018);Yang et al (2004);Yang et al (2003).Identifying the species that reduces and the species that oxidizes Acar and Tarhan (2007)Eybe and Schmidt (2001);Messersmith (2014);Niaz (2002);Niaz and Chacón (2003);Schmidt and Volke (2003); Schultz(2008); Supasorn (2015); Rosenthal and Sanger (2012).…”
mentioning
confidence: 99%
“…In their research, Eveillard et al (2017) concluded that Master's students expressed positive opinions about that they participated actively in the group work and group work facilitated interpersonal communication in PBL approach concerning antibiotic exposure and bacterial resistance in human and veterinary medicine. In their research of Tarkın and Uzuntiryaki-Kondakcı (2017), they concluded that the secondary school students had positive opinions about that chemistry lessons were more interesting and enjoyable via case-based instruction concerning the topic of electrochemistry. In this research, some students also expressed negative opinions such as that the method was unfamiliar.…”
Section: Introductionmentioning
confidence: 99%